Nitrile-substituted 2-(oxazolinyl)-phenols: minimalistic excited-state intramolecular proton transfer (ESIPT)-based fluorophores. Issue 27 (15th May 2020) - Göbel, Dominik; Duvinage, Daniel; Stauch, Tim; Nachtsheim, Boris J.
Abstract : Nitrile-substituted 2-(oxazolinyl)-phenols are efficient single-benzene, excited-state intramolecular proton transfer (ESPIT)-based fluorophores. Abstract : Herein, we present minimalistic single-benzene, excited-state intramolecular proton transfer (ESIPT)-based fluorophores as powerful solid-state emitters. The very simple synthesis gave access to all four regioisomers of nitrile-substituted 2-(oxazolinyl)-phenols ( M W = 216.1). In respect of their emission properties they can be divided into aggregation-induced emission enhancement (AIEE) luminophores (1-CN and 2-CN ), dual state emission (DSE) emitters (3-CN ) and aggregation-caused quenching (ACQ) fluorophores (4-CN ). Remarkably, with compound 1-CN we discovered a minimalistic ESIPT-based fluorophore with extremely high quantum yield in the solid state Φ F = 87.3% at λ em = 491 nm. Furthermore, quantum yields in solution were determined up to Φ F = 63.0%, combined with Stokes shifts up till 11.310 cm −1 . Temperature dependent emission mapping, crystal structure analysis and time-dependent density functional theory (TDDFT) calculations gave deep insight into the origin of the emission properties.